Urgensi Pendidikan Perempuan Dalam Menghadapi Masyarakat Modern: The Urgency of Women's Education in Facing Modern Society - Ainiyah, Qurrotul (Universitas Muhammadiyah Sidoarjo, 2017)
Ladies as mothers for your children, education for women is not only necessary, but it is very important to get attention. Education, stems from families, and the role of ladies as mothers is significant. In addition, the views of Sufis and philosophers about the complementary relationship between masculine and feminine traits in human beings, should be a grip for educators. Education must be balanced between affection and firmness, between forgiveness and discipline enforcement. Women in the modern era are development stakeholders, therefore development implementation should emphasize the importance of women's empowerment efforts. Involvement of women community to participate in providing input in formulation and supervision. So they can actively participate in the development process to realize a just and prosperous society, without any kind of oppression.